2019
DOI: 10.1002/acm2.12561
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of mixed energy partial arcs for volumetric modulated arc therapy for prostate cancer

Abstract: Purpose The purpose of this work was to investigate the dosimetric impact of mixed energy (6‐MV, 15‐MV) partial arcs (MEPAs) technique on prostate cancer VMAT plans. Methods This work involved prostate only patients, planned with 79.2 Gy in 44 fractions to the planning target volume (PTV). Femoral heads, bladder, and rectum were considered organs at risk. This study was performed in two parts. For each of the 25 patients in Part 1, two single‐energy single‐arc plans, a 6 MV‐SA plan and a 15 MV‐SA plan, and a t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…(12) and (13) is the non-negative continuous variable, which represents aperture weight in MUs for energy X at control point k. As shown in Eqs. (15) and (16), this variable is bounded by an upper, U mu ; and a lower, L mu ; aperture weights, which are defined by the mechanical limitations of the linac for a given gantry speed schedule. The aperture weight remains constant as the gantry rotates from k th control point to k + 1.…”
Section: E Mixed Integer Linear Programming Mp -Vmat Modelmentioning
confidence: 99%
See 3 more Smart Citations
“…(12) and (13) is the non-negative continuous variable, which represents aperture weight in MUs for energy X at control point k. As shown in Eqs. (15) and (16), this variable is bounded by an upper, U mu ; and a lower, L mu ; aperture weights, which are defined by the mechanical limitations of the linac for a given gantry speed schedule. The aperture weight remains constant as the gantry rotates from k th control point to k + 1.…”
Section: E Mixed Integer Linear Programming Mp -Vmat Modelmentioning
confidence: 99%
“…Only a few studies have investigated dosimetric outcome of mixed photon energies for VMAT. Both studies indicated better sparing of OARs in comparison to the single energy VMAT . Currently, all VMAT treatments have also been limited to a single photon energy beam.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…Therefore, the planner needs to decide the ideal beam energy when designing a treatment plan, and it may also vary with the gantry angle. Previous studies showed potential advantages of mixed energy photons in improving plan quality in prostate and breast plans (3)(4)(5)(6)(7)(8)(9). However, none of these studies have fully demonstrated the concept of photon energy synthesis systemaically and its potential advantages in radiation treatment.…”
Section: Introductionmentioning
confidence: 99%